Counseling minority adolescent girls in a predominately White middle school setting: perceptions of empowerment groups for academic success (EGAS) model - Hilton-Pitre, Twana Y., author; Carlson, Laurie, advisor; Lewis, Chance W., advisor; Banning, James H., committee member; Sanders-Okine, Eulanda, committee member (Colorado State University. Libraries, 2007)
The purpose of this study was to explore the perceptions of minority adolescent girls in a predominately White middle school setting regarding the influence of the Empowerment Groups for Academic Success (EGAS) (2005) model. The EGAS model is a group counseling approach that takes into account the influence of environmental, social, and psychological factors on academic performance for adolescents. The goal for this study was to describe the experiences of minority adolescent eighth grade girls in a predominately White middle school setting who participated in the EGAS model. As a phenomenological research design, qualitative research methods were employed as the primary means of collecting and analyzing data. The research design involved in-depth individual interviews, journaling, and observations of a purposeful sample of eight minority eighth grade girls. Participants' perceptions and experiences were captured through self-reports in diaries, individual interviews, and the researcher's field notes during eight weekly sessions for 45 minutes. This research presented the adolescents' perceptions of their experiences during EGAS and the outcome of EGAS (i.e. personal, social, academic, and career development). Themes emerged during this study which included: social support, racial relations, identity development, conflict resolution, and career preparation. Finally, the data were analyzed within and cross-cases for comparisons and contrasts among the adolescents regarding their experiences. The findings of this study inform recommendations for middle school counselors, administrators, and teachers who work with minority adolescents. This study has expanded the applicability of the EGAS model in several ways: 1) it can be utilized in a suburban setting; 2) it is appropriate with minority students in a predominately White school population; and 3) it can be implemented with middle school minority adolescents. In all, this research provides lessons learned and insights gained from implementing the ESAG model with minority adolescent girls in a predominately White middle school.
Keywords: academic guidance counseling; secondary education; school counseling